La metáfora del viaje en Un viaje de novios de Emilia Pardo Bazán - Kidakou, Antoine Bouba (Acta Hispanica, 2015)
Within the vast corpus of the nineteenth century Spanish narrative, Emilia Pardo Bazán’s Un viaje de novio, deserve a different consideration due to a particular style adopted by the author and the consideration of travel as an allegory of life. The author departs, hence fore, from the way how travel was understood in the nineteenth century when writers based their travel writings or novels on the scientific and educational aspects. Pardo Bazan explores the transcendental aspect of travel fact and this paper studies the different techniques used by the writer to develop the metaphor of travel considering the geographical movement as an internal trip. The subjective and progressive transformation of the main protagonist, according to the itinerary of the trip, is studied as that internal journey.